MFAP5 as a promising biomarker for connective tissue disease-associated interstitial lung disease - Dai, Yufang; Zhang, Jiaqian; Bai, Xiufeng; Wu, Shasha; Chen, Yanqiong; Mou, Dachao; Wang, Yun; Zhu, Yunlong; Liu, Yi (Frontiers in Immunology, 2025)
Interstitial lung disease (ILD), a common and severe complication of connective tissue disease (CTD), can cause progressive lung function decline and even death. However, current biomarkers for diagnosing and predicting CTD-ILD are unsatisfactory. Here, we identify a new diagnostic and prognostic biomarker for CTD-ILD. We used comparative transcriptomic sequencing and bioinformatics analysis of the Gene Expression Omnibus (GEO) database to identify upregulated genes in lung fibroblasts of systemic sclerosis-associated ILD. Peripheral blood, bronchoalveolar lavage fluid (BALF), and lung tissue samples from healthy donors, CTD patients, and CTD-ILD patients were collected. Immunohistochemistry, immunofluorescence, and ELISA were used to validate the expression levels of candidate biomarkers. Microfibril-Associated Protein 5 (MFAP5) is upregulated in the lung tissue of ILD patients. Meanwhile, serum and BALF MFAP5 levels in CTD-ILD patients are significantly elevated compared to those in CTD patients without ILD and healthy controls, showing positive correlations with the extent of ILD. involvement and multiple inflammatory markers, along with a negative correlation with anti-inflammatory immunoglobulin IgG. MFAP5 has 89.53% specificity in differentiating CTD-ILD from CTD without ILD. Furthermore, in the bleomycin (BLM)-induced mouse model, MFAP5 mRNA and protein expression were increased. These findings suggest that MFAP5 levels are elevated in CTD-ILD patients and may serve as a biomarker for diagnosing and predicting CTD-ILD.